Can it be too close? The impact of the proximity of the Polish-German border on local development in Poland in the process of European integration - Aksztejn, Wirginia; Swianiewicz, Paweł; Szmigiel-Rawska, Katarzyna (Rozwój Regionalny i Polityka Regionalna, 2020)
The aim of this study was to investigate the dynamics of local development in the Polish-German borderland in the process of European integration. Taking the perspective of the economically weaker partner (Poland) and its inner market, fiscal and socio-economic indicators were used to depict both spatial and time dimension of the phenomenon. The analysis showed that the dynamics of local economy, foreign investment and labour market have been changing with the advancement of debordering process and had a non-linear character. Furthermore, the legal barriers earlier imposed by the state border were replaced by other limitations for the new common market – more socio-economic in nature. As a result the immediate neighbourhood of the border was the first beneficiary of the European integration initiated in the nineties and the first to experience its drawbacks.